The Social Services : The immediate problem and the way forward (London : The Socialist Medical Assocation)
1944 1944 1940s 34 pages centres, and also in the evening, and these experiments might well be extended. While at present it is usually not possible to continue the service of meals into the evening, in better times this might be tried with advantage, and such centres might become the basis of more comprehensive community centres. 6. Holidays. Holidays have hitherto been considered as purely private affairs. Those who were lucky enough, before the war, to get a holiday and to have money to spend, were free to arrange it, but for those less fortunate who stayed at home there was little provision, especially in towns where open spaces are in short supply. For the housewife holidays have often meant increased responsibility, and for children they have often provided little more than increased opportunities to get into trouble. During the war, for two main reasons, the recognition that holidays are a human need for which social provision should be made, has been forced on the authorities. First, the problem of fatigue among factory and Civil Defence workers has led to the provision of a few Rest Homes, not, so far, by the Government, but by voluntary agencies with Government approval. Secondly, the need to prevent travelling has led to "Holidays-at-Home" schemes in towns, most of which have been a great popular success. There 13 15X/2/464/1